Click Beetle Mitogenomics with the Definition of a New Subfamily Hapatesinae from Australasia (Coleoptera: Elateridae) - Dominik Kusy; Michal Motyka; Ladislav Bocak (Insects, 2020)
Elateridae is a taxon with very unstable classification and a number of conflicting phylogenetic hypotheses have been based on morphology and molecular data. We assembled eight complete mitogenomes for seven elaterid subfamilies and merged these taxa with an additional 22 elaterids and an outgroup. The structure of the newly produced mitogenomes showed a very similar arrangement with regard to all earlier published mitogenomes for the Elateridae. The maximum likelihood and Bayesian analyses indicated that Hapatesus Candèze, 1863, is a sister of Parablacinae and Pityobiinae. Therefore, Hapatesinae, a new subfamily, is proposed for the Australian genera Hapatesus (21 spp.) and Toorongus Neboiss, 1957 (4 spp.). Parablacinae, Pityobiinae, and Hapatesinae have a putative Gondwanan origin as the constituent genera are known from the Australian region (9 genera) and Neotropical region (Tibionema Solier, 1851), and only Pityobius LeConte, 1853, occurs in the Nearctic region. Another putative Gondwanan lineage, the Afrotropical Morostomatinae, forms either a serial paraphylum with the clade of Parablacinae, Pityobiinae, and Hapatesinae or is rooted in a more terminal position, but always as an independent lineage. An Eudicronychinae lineage was either recovered as a sister to Melanotini or as a deep split inside Elaterinae and we herein transfer the group to Elaterinae as Eudicronychini, a new status. The mitochondrial genomes provide a sufficient signal for the placement of most lineages, but the deep bipartitions need to be compared with phylogenomic analyses.